The theory of public diplomacy: history and modernity - Airapetova, Ruzanna (YSU Journal of International Affairs, 2021)
The article presents the historical development of public diplomacy. The study presents the development of the theory of public diplomacy in the context of the transformation of the main constituent elements. In this context, the differences and similarities between public diplomacy and propaganda, cultural diplomacy and strategic communication were considered. The role of non-governmental actors in the development of public diplomacy was also noted.
Keywords: public diplomacy; soft power; national branding; strategic communication; cultural diplomacy; propaganda